2022
DOI: 10.3389/fpls.2022.850062
|View full text |Cite
|
Sign up to set email alerts
|

A Moss 2-Oxoglutarate/Fe(II)-Dependent Dioxygenases (2-ODD) Gene of Flavonoids Biosynthesis Positively Regulates Plants Abiotic Stress Tolerance

Abstract: Flavonoids, the largest group of polyphenolic secondary metabolites present in all land plants, play essential roles in many biological processes and defense against abiotic stresses. In the flavonoid biosynthesis pathway, flavones synthase I (FNSI), flavanone 3-hydroxylase (F3H), flavonol synthase (FLS), and anthocyanidin synthase (ANS) all belong to 2-oxoglutarate/Fe(II)-dependent dioxygenases (2-ODDs) family, which catalyzes the critical oxidative reactions to form different flavonoid subgroups. Here, a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 95 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…The phenylalanine content in the HAD group increases under high-temperature stress, thereby promoting the production of polyphenols and flavonoids. This is consistent with the findings of Wang et al (2022), where Arabidopsis subjected to high-temperature stress showed an increase in the expression of flavonoids [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…The phenylalanine content in the HAD group increases under high-temperature stress, thereby promoting the production of polyphenols and flavonoids. This is consistent with the findings of Wang et al (2022), where Arabidopsis subjected to high-temperature stress showed an increase in the expression of flavonoids [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, 2-ODD expression in mutant plants increased antioxidant capacity and improved tolerance to salt, drought, UV, and oxidative stresses. These results suggested that 2-ODD is a crucial enzyme involved in the adaptation of P. nutans to harsh polar environments through anthocyanins and flavonol accumulation [100].…”
Section: Manipulation Of Anthocyanin Biosynthesis Genes To Improve Bo...mentioning
confidence: 80%
“…This is a highly conserved N-terminal region of proteins with 2-oxoglutarate/Fe(II)-dependent dioxygenase activity and is widely distributed in nature [ 54 ]. It can promote the accumulation of flavonoids and positively regulate plant abiotic stress tolerance [ 55 ]. Perhaps the response of RrATG18e to C. fructicola infection in R. roxburghii fruits is closely related to this special conserved domain.…”
Section: Discussionmentioning
confidence: 99%